Resource sharing and incentive mechanism for multi-access edge computing networks - Liangjun SONG; Gang SUN; Jian SUN; Hongfang YU (Tongxin xuebao)
A tripartite incentive-enabled edge device resource sharing algorithm was proposed to manage and allocate the shared resources for the “cloud-edge-end” three-tier edge network architecture.Considering the single-point network congestion, network-wide coverage constraint, limited resource constraint and transmission cost constraint, the edge devices were abstracted into different functional nodes to design a convex envelope-based shared node (CESN) selection algorithm to achieve a full-coverage, low-energy shared resource deployment scheme.Secondly, to address the additional cost problem caused by allocating shared resources on edge devices, a tripartite sharing incentive mechanism was designed based on the shared resource leasing model, which guaranteed the long-term and stable participation of edge devices in the sharing mechanism.The simulation results show that the proposed algorithm significantly improves the system energy consumption and node revenue compared to the existing algorithms.